A Refined Green’s Function Estimate of the Time Measurable Parabolic Operators with Conic Domains - Kim, Kyeong Hun; Lee, Kijung; Seo, Jinsol (Potential Analysis, 2022)
We present a refined Green’s function estimate of the time measurable parabolic operators on conic domains that involves mixed weights consisting of appropriate powers of the distance to the vertex and of the distance to the boundary.
Keywords: Conic domains; Green’s function estimate; Stochastic parabolic equation